First description of the female of the Asian leafhopper genus Stenolora Zhang, Wei & Webb, 2006 (Hemiptera: Cicadellidae: Deltocephalinae: Stegelytrini) - Duan, Keting; Webb, Mick; Xing, Jichun (Zootaxa, 2025)
The Chinese species Stenolora abbreviata Zhang, Wei & Webb, 2006 (Cicadellidae: Deltocephalinae: Stegelytrini) is redescribed, including the female of the genus, described for the first time. We also provide photos of the male habitus and genitalia for the first time.